Dynamics of freight cars on bogies model 18-1711 with different wedge de-signs of spring suspension - Mankevych, N. B. (Science and Transport Progress, 2014)
Purpose. To analyze the results of the study of dynamic parameters of a gondola car, model 12-1704-04 with axle load 23.5 ton in bogies, models 18-1750 and two gondola cars, model 12-1905 with axial load of 25 ton, one of which is equipped with bogies, model 18-1711 with friction wedges of spring suspension with spatial form with increased angle to the horizontal line of intersection of the contact surfaces between the wedge and bolster, the other gondola car, model 12-1905 is equipped with bogies of the same model on which the friction wedges fitted with a flat form of contact surface. It has an angle of inclination like a wedge of bogie, model 18-100. On the basis of the obtained results to draw conclusions about the feasibility of unification design bogie bolster, model 18-1711 with bogie, model 18-100 by contact surfaces with elements of spring suspension. Methodology. Research on dynamic performance of cars was performed during running dynamic tests of specimens of freight cars in experimental train consisting of two locomotives, a laboratory, and three gondola cars of the above mentioned models. Findings. Main results of dynamic studies are presented as graphs of indicators on the speed of the train and the experimental evidence that the freight gondola cars on bogies, model 18-1711 with flat-shaped wedges, in most cases are better than the others. Originality. Research results of cars on bogies, model 18-1711 were obtained. They let assess the dependence of the dynamic performance of the car from the design of the friction wedges of spring suspension. Practical value. Cast parts of bogie, model 18-1711 with 25 ton axle load can be used as a replacement of defective parts of bogie, model 18-100 and its analogs.